The Impact of Inflammatory Immune Reactions of the Vascular Niche on Organ Fibrosis - Zhou, Hong-Yan; Sui, Hua; Zhao, Yang-Jianing; Qian, Hong-Jie; Yang, Nan; Liu, Lu; Guan, Qing; Zhou, Yue; Lin, Hong-Li; Wang, Da-Peng (Frontiers in Pharmacology, 2021)
Inflammation is a type of defense response against tissue damage, and can be mediated by lymphocytes and macrophages. Fibrosis is induced by tissue injury and inflammation, which leads to an increase in fibrous connective tissue in organs and a decrease in organ parenchyma cells, finally leading to organ dysfunction or even failure. The vascular niche is composed of endothelial cells, pericytes, macrophages, and hematopoietic stem cells. It forms a guiding microenvironment for the behavior of adjacent cells, and mainly exists in the microcirculation, including capillaries. When an organ is damaged, the vascular niche regulates inflammation and affects the repair of organ damage in a variety of ways, such as via its angiocrine function and transformation of myofibroblasts. In this paper, the main roles of vascular niche in the process of organ fibrosis and its mechanism of promoting the progress of fibrosis through inflammatory immunoregulation are summarized. It was proposed that the vascular niche should be regarded as a new therapeutic target for organ fibrosis, suggesting that antifibrotic effects could be achieved by regulating macrophages, inhibiting endothelial-mesenchymal transition, interfering with the angiocrine function of endothelial cells, and inhibiting the transformation of pericytes into myofibroblasts, thus providing new ideas for antifibrosis drug research.